1951
DOI: 10.1111/j.1651-2227.1951.tb15802.x
|View full text |Cite
|
Sign up to set email alerts
|

The Skeletal Age in Diabetic Children

Abstract: causcs practically no discomfort. The "hyalase" helps to rctlucc the resistance of the tissues to the injection of contrast medium, and the spread and absorption of the medium, and consequently the excretion is also thus considerably accelerated. Using this technique, excellent urograms, fully comparable with those obtained with the intravenous method, were made.The method has been tried out in clinical practice during the past year and has proved to be a valuable aid in the examination of kidneys and urinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1952
1952
1972
1972

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…She also noted that the longer the duration of diabetes the greater the tendency to retardation. In other series, though some children had accelerated and some retarded bone ages, the majority were within normal limits (Hernberg and Heikel, 1951). Atlas controls were used in all these series.…”
Section: Resultsmentioning
confidence: 99%
“…She also noted that the longer the duration of diabetes the greater the tendency to retardation. In other series, though some children had accelerated and some retarded bone ages, the majority were within normal limits (Hernberg and Heikel, 1951). Atlas controls were used in all these series.…”
Section: Resultsmentioning
confidence: 99%
“…He discussed the possible etiology of these changes and their relationship to benign hypertrophy. Skeletal age in diabetic children was dealt with by Hernberg and Herkel (80). He found areolar size genetically limited and independent of size.…”
Section: Fulton (44) Compared Dental Caries In New Zealand and The Unmentioning
confidence: 99%
“…It summarized current vital rates and age characteristics of the world by regions-population, births, deaths, marriages, and migrations. 80. He found that most of the primary ossification centers appeared before the end of the fourth month and almost all of these between the seventh and twelfth weeks of embryonic life.…”
mentioning
confidence: 99%